Spatiotemporal gait parameters and ground reaction forces in stroke survivors with diabetic peripheral neuropathy / Nurul Amirah Mustapa - Mustapa, Nurul Amirah (2017)
The aim of this study is to investigate the changes of spatiotemporal gait parameters, gait variability, and ground reaction forces (GRFs) in stroke survivors with diabetic peripheral neuropathy (DPN). Ten stroke survivors with DPN (SDPN), 10 stroke survivors without DPN (S), and 10 healthy controls (HC) were participated in this case-control cross-sectional study. Spatiotemporal gait parameters, gait variability and GRFs were recorded using the Nexus Vicon motion analysis system. A total of 16 retro-reflective spherical markers were placed bilaterally on the certain anatomical landmarks and participants were asked to walk at a habitual speed within 5 meters of the platform. Raw marker data was collected using the camera motion analysis system were filtered at 10 Hz using a low-pass fourth-order Butterworth filter for data analysis. The Kruskal-Wallis test was used to analyse gait parameters, gait variability, and GRFs, and the Spearman's rank-order correlation coefficients test was used to identify the correlations between the muscle strength (Motricity Index (MI)), stroke severity (Stroke Rehabilitation Assessment of Movement (STREAM)), and functional balance (Berg Balance Scale (BBS)) variables with spatiotemporal gait parameters and GRFs. This study found that longer stride time (temporal gait parameter) instead of the shorter stride length (spatial gait parameter), greater gait variability, and slower cadence on the paretic and non-paretic side in SDPN compared to S and HC. This study also found significant alteration of mediallateral forces of the non-paretic side and vertical forces of the paretic side in SDPN compared to other groups. In addition, there were smaller magnitude of anteriorposterior forces, medial-lateral forces, and vertical forces in SDPN compared to other groups. Gait parameters were significantly correlated with MI, STREAM, and BBS (r = ± 0.63 - 0.91; p < 0.05) in SDPN. Gait parameters also were significantly correlated with BBS (r = ± 0.72 - 0.85; p < 0.05) in S. These findings suggested that gait parameters, gait variability, and GRFs are affected in SDPN. Gait was further affected by impairments of the muscle strength, severity of stroke, and functional balance performance.